2017
DOI: 10.1084/jem.20161924
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin releasing hormone receptor 2 exacerbates chronic cardiac dysfunction

Abstract: Prognosis of patients with chronic heart failure remains poor, emphasizing the need to identify additional pathophysiological factors. Tsuda et al. show that Crhr2 activation causes cardiac dysfunction and suggest Crhr2 blockade is a promising therapeutic strategy for chronic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 69 publications
2
35
0
Order By: Relevance
“…Despite the gender differences observed in other peptides from the Ucn family and CRHR2, [39][40][41] there were no gender-related differences in plasma Ucn-2 levels in patients with heart disease, 19,21 nor in the role of CRHR2 in HF. 20 This was also true in our small cohort of patients.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Despite the gender differences observed in other peptides from the Ucn family and CRHR2, [39][40][41] there were no gender-related differences in plasma Ucn-2 levels in patients with heart disease, 19,21 nor in the role of CRHR2 in HF. 20 This was also true in our small cohort of patients.…”
Section: Discussionsupporting
confidence: 66%
“…Only three studies have measured plasmatic Ucn-2 levels in human patients with cardiovascular disorders, reporting significantly different (up to 1000-fold) concentrations in their cohorts. [18][19][20] However, Ucn-2 seems to be activated on circulating and inflammatory cells (buffy coat), which mediate vascular and myocardial remodelling mechanisms. 38 Also, we did not find any differences in the lung expression of Ucn-2 and CRHR2 in experimental PAH, suggesting a more profound dysregulation of Ucn-2/CRHR2 signalling in the RV as compared with the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 A non-biased quantitative RT-PCR (qRT-PCR) analysis, which determined the gene copy numbers of 475 GPCRs in adult murine cardiomyocytes, revealed that CRHR2 was the 4th most abundantly expressed GPCR in cardiomyocytes. 34 In vitro, UCN2 and UCN3 significantly increase myocyte contractility in a dose-dependent manner, as characterized by increased fractional shortening and peak systolic Ca 2+ transients. 35 In rabbit and mouse ventricular myocytes, UCN2 mediates inotropic and lusitropic effects via the cAMP-and Ca 2+ /calmodulin-CaMKII signaling pathways, and also induces arrhythmogenic effects.…”
Section: Cardiac Effects Of Crhrsmentioning
confidence: 95%
“…39 Experiments involving administration of UCNs have revealed the inotropic effects of CRHR2 in the heart, but in conventional CRHR2 −/− mice and in cardiomyocyte-specific CRHR2 deficiency, basal cardiac function remains unaffected. 31,34 Thus, the physiological role of CRHR2 in basal cardiac function is still unclear.…”
Section: Crhrsmentioning
confidence: 99%